Relationship of information and signs - Yakovyv, Ihor (Collection "Information Technology and Security", 2012)
The development of information technologies for knowledge processing has led to an increase in interest in a general theory of information. A new conception of essence of information and of signs, the nature of their relationships is presented in this article.